Answer:
a. (-3, 2).
b. √65
c. (x + 3)^2 + (y - 2)^2 = 65
Step-by-step explanation:
a. The center is the midpoint of the diameter PQ.
= (-10+4)/2, (-2+6)/2
= (-3, 2).
b. The radius is the distance from the center to a point on the circle.
Take the point (4, 6):
The radius = √((-3-4)^2 + (2-6)^2)
= √65.
c. The equation of the circle is:
Using the standard form
(x - h)^2 + (y - k)^2 = r^2 where (h, k) is the center and r = the radius:
it is (x - (-3)^2 + (y - 2) = 65
= (x + 3)^2 + (y - 2)^2 = 65.
Answer:
It's linear
Step-by-step explanation:
Im not sure wym but i think the answer is 20
Answer:
(x−2)(x−2)(x−2)
Step-by-step explanation:Answer:
(x−2)(x−2)(x−2)
Step-by-step explanation:Answer:
(x−2)(x−2)(x−2)
Step-by-step explanation:Answer:
(x−2)(x−2)(x−2)
Step-by-step explanation:vvAnswer:
(x−2)(x−2)(x−2)
Step-by-step explanation:Answer:
(x−2)(x−2)(x−2)
Step-by-step explanation:vAnswer:
(x−2)(x−2)(x−2)
Step-by-step explanation:Answer:
(x−2)(x−2)(x−2)
Step-by-step explanation:vvAnswer:
(x−2)(x−2)(x−2)
Step-by-step explanation:Answer:
(x−2)(x−2)(x−2)
Step-by-step explanation:Answer:
(x−2)(x−2)(x−2)
Step-by-step explanation:Answer:
(x−2)(x−2)(x−2)
Step-by-step explanation:Answer:
(x−2)(x−2)(x−2)
Step-by-step explanation:Answer:
(x−2)(x−2)(x−2)
Step-by-step explanation:Answer:
(x−2)(x−2)(x−2)
Step-by-step explanation:Answer:
(x−2)(x−2)(x−2)
Step-by-step explanation:v